THE METHODOLOGY OF USING GAME ACTIVITIES TEACHING A FOREIGN - Habibullayeva, Odinakhan Marufkhan qizi (Educational Research in Universal Sciences, 2023)
In the following article is highlighted the study of gaming technology in the classroom in the 6 grade. In the sake of the main tasks of a teacher at an early and average stage of teaching children a foreign language is to make this subject more interesting and beloved. Special attention is paid to the use of foreign language lessons the strange language of game technologies, in particular role-playing games, which is an important method for stimulating the motivation of educational and cognitive activity of schoolchildren. The characteristic features of the methodological structure of the role-playing game are described.